2021
DOI: 10.46519/ij3dptdi.991955
|View full text |Cite
|
Sign up to set email alerts
|

Fi̇zi̇k, Ki̇mya Ve Bi̇yoloji̇ Öğretmenleri̇ni̇n 3-Boyutlu Kati Model Tasarim Ve Kullanim İhti̇yaçlarina Genel Bi̇r Bakiş

Abstract: Bu araştırma ile fizik, kimya ve biyoloji öğretmenlerinin 3B katı model tasarımına ve tasarlayacakları modellerin öğretim süreçlerinde kullanımına yönelik ihtiyaçlarının belirlenmesi amaçlanmaktadır. Durum çalışması yöntemi ile yürütülen bu araştırmanın örneklemini 16 farklı ilde görev yapan 27 fizik, 36 kimya ve 40 biyoloji olmak üzere toplamda 103 (66 kadın, 37 erkek) öğretmen oluşturmaktadır. Veri toplama aracı olarak, araştırmacılar tarafından geliştirilen çevrimiçi "Fen Öğretiminde 3-Boyutlu Modellerin Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The interaction between the educator and the student will increase even more with the increase in the widespread use of this technology thanks to the decreasing investment costs and it will be easier for students to gain creativity and innovative thinking skills by transforming what they envision into tangible objects (Kökhan & Özcan, 2018). When the studies (Aslan et al, 2021;Çoklar & Çekirge, 2020;Çopur & Türkdoğan, 2021;Doğan & Uluay, 2020;Karagöz & Şahin-Çakır, 2020;Topçuoğlu et al, 2021) in the literature in recent years are examined, it has been determined that 3D printing technology is increasingly used in education. It is stated in the literature that the use of 3D printers in educational environments may have positive effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the educator and the student will increase even more with the increase in the widespread use of this technology thanks to the decreasing investment costs and it will be easier for students to gain creativity and innovative thinking skills by transforming what they envision into tangible objects (Kökhan & Özcan, 2018). When the studies (Aslan et al, 2021;Çoklar & Çekirge, 2020;Çopur & Türkdoğan, 2021;Doğan & Uluay, 2020;Karagöz & Şahin-Çakır, 2020;Topçuoğlu et al, 2021) in the literature in recent years are examined, it has been determined that 3D printing technology is increasingly used in education. It is stated in the literature that the use of 3D printers in educational environments may have positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies; middle school students (Gürel-Taşkıran, 2019;Küçüksolak, 2019), prospective teachers (Güleryüz et al, 2019;2020;Karagöz & Şahin-Çakır, 2020), high school students (Küçüksolak , 2019), preschool children (Yüksel, 2015) were studied. When the studies made with 3D printing technology in science education are examined in the literature; determination of science teacher candidates' opinions about 3D printers (Karagöz & Şahin-Çakır, 2020), 3D printing technology in education and some examples of 3D printer technology materials applied in chemistry education (Topçuoğlu et al, 2021), the effects of 3D printer and robotic coding applications on 21st-century learning skills, STEM awareness and STEM teacher self-efficiency of preservice teachers (Güleryüz, 2020), pre-service science teachers' learning and implementation experiences with 3D Technologies (Doğan & Uluay, 2020), an overview of the 3D solid model studies such as design and usage needs of physics, chemistry, and biology teachers (Aslan et al, 2021) were found. It is thought that this research, in which both the academic achievements of the students and their views about the activities made using 3D printing technology, will contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%